Assessing the Scope of Impact, Impact Measures and Factors Influencing Social Enterprise Impact Measure Selection across Africa - Adomdza, G.K.; Asiedu, M.; Lartey, A.S.D.; Lawal, A.B. (Journal of Advocacy, Research and Education, 2020)
Social enterprises have been identified as one of the ways of tackling some of the most challenging social problems around the globe. Despite, being touted as indispensable to the developmental agenda of most developing economies, especially across Africa, very little effort has been made to understand the scope of impact and impact assessment measures adopted to evaluate the activities in the space in the continent. The current study is an inquiry into the mechanisms adopted by SEs in their impact assessments within Africa. Additionally, the research focuses on the scope of the impact of SEs across the continent. The results revealed an imbalance in the use of the two categories of impact measures; “individual-based impact measures” and “non-financial impact measures”. SEs have relied more on “what we do” and numbers to justify their impact in several parts of the continent. Additionally, the research also revealed that some of the impact areas of SEs included poverty and inequality; education and technology; entertainment; child empowerment; girl and women empowerment; youth empowerment; and social welfare and disability. The research recommends that SEs should endeavor to measure their impact from a comprehensive perspective, to align their activities and measures to the broader national and/or global agenda.
Research Article
Keywords: Africa; impact measures; impact; social enterprise